2020
DOI: 10.3390/pr8101314
|View full text |Cite
|
Sign up to set email alerts
|

Some Physical Properties and Mass Modelling of Pepper Berries (Piper nigrum L.), Variety Kuching, at Different Maturity Levels

Abstract: Pepper berry (Piper nigrum L.) is known as the king of spices and has sharp, pungent flavour and aroma. In this study, the physical properties (weight, dimensions, sphericity, volume, surface area, and projected area) were measured, and the mass of pepper berries of the Kuching variety at different maturity levels (immature, mature, and ripe) was predicted using four models: linear, quadratic, s-curve, and power. When the models were based on volume and projected area, the mass could be predicted with maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…The actual volume (V) of the fruit was determined by using the water displacement method (Akar & Aydin, 2005). The geometric mean diameter (GMD), sphericity (ϕ), and aspect ratio (AR) were determined by using the following equations used by Megat Ahmad Azman et al (2020). GMDgoodbreak=LWT13 normalΦgoodbreak=()()LWT1/3/normalL ARgoodbreak=normalL/normalW The projected area of a single fruit is a good indicator of mass.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The actual volume (V) of the fruit was determined by using the water displacement method (Akar & Aydin, 2005). The geometric mean diameter (GMD), sphericity (ϕ), and aspect ratio (AR) were determined by using the following equations used by Megat Ahmad Azman et al (2020). GMDgoodbreak=LWT13 normalΦgoodbreak=()()LWT1/3/normalL ARgoodbreak=normalL/normalW The projected area of a single fruit is a good indicator of mass.…”
Section: Methodsmentioning
confidence: 99%
“…The projected areas of strawberries in three perpendicular dimensions viz., PA L , projected area perpendicular to the length (mm 2 ); PA W , projected area perpendicular to the width (mm 2 ); PA T , projected area perpendicular to the thickness (mm 2 ), were measured by using a camera and Fiji ImageJ. The criteria projected area (CPA) was determined by using the Equation (4) used by Megat Ahmad Azman et al (2020). CPAgoodbreak=()PALgoodbreak+PAwgoodbreak+PAT/3 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Azman et al [10] studies the physical properties and mass modeling of pepper berries at different maturity levels. It was found that the quadratic model was best fitted for mass prediction at all mass maturity levels (immature, mature, and ripe).…”
Section: Application Of Mathematical Modeling and Computer Simulations In Postharvest Technologymentioning
confidence: 99%
“…This special issue consists of three sections, focusing on food storage and preservation technologies [1][2][3][4], food processing technologies [5][6][7][8], and the applications of advanced mathematical modeling and computer simulations [9][10][11]. We wish to acknowledge the expert contributions of all authors here.…”
mentioning
confidence: 99%